PKM Farmer Group Matan Lalanglinggah Application of Fermented Feed Technology and Processing of Livestock Waste Into Quality Organic Fertilizer and Economic Value - Yan Tonga; I Gede Sutapa; I Ketut Agung Sudewa; Ignasius Ghari Jati; Desantro Tamo (Asian Journal of Community Services, 2023)
The main potential developed and as a support for family income by the people of Lalanglinggah Village is in the livestock sector (pigs, goats, and cows), in the agricultural sector (food crops such as: rice and bananas), and in the plantation sector such as: coconut, cocoa, and porang. (Lalanglinggah Village Profile, 2019). The problems of partners are that they do not have knowledge in efforts to increase the productivity of goats and pigs, do not have knowledge and skills in making effective and efficient fermented feed with Bioster technology and processing livestock and agricultural waste into quality and economic value organic. The methods used were survey, interview, discussion, counseling/training. The resulting output is that partners understand about efforts to increase the productivity of goats and pigs, making fermented feed, quality and valuable organic fertilizer.